Molecular characterization and Freedom to Operate analysis of maize hybrids from genetically modified and Colombian varieties (2016)
Spodoptera frugiperda is one of the most common pests in maize crops, causing important losses in Colombia. The development of insect resistant crops is an alternative to conventional pest control methods. HERCULEX® I is a transgenic maize line with resistance to lepidopteran insects and tolerance to phosphinothricin herbicides, conferred by genes cry1F and pat, respectively. In Colombia, the National Federation of Cereal and Legume Growers (FENALCE) has carried out mendelian crosses between Colombian maize genotypes and HERCU- LEX® I, with the aim of integrating the genetic elements of the transgenic line into national varieties. Three hybrids were obtained which potentially carry such constructs. In the present study, the hybrid lines and their parental lines were characterized at the molecular level. Leaf tissue was tested for presence or absence of the genes cry1F and pat and their expression as mRNA and respective proteins Cry1F and Pat. Results show that the three hybrids indeed carry the HERCULEX® I constructs. RT-PCR and ELISA analysis showed transcription of the genes and presence of the proteins. An initial approach to the Freedom to Operate analysis was carried out for HERCU- LEX® I in Colombia.